Awareness on cervical cancer and practice of pap smear test among the married women of Changunarayan municipality - Bharati, Mamata; Chalise, Gita Dhakal; KC, Ambu; Khadka, Sushmita; Bharati, Nisha; Lakhaju, Laxmi (Journal of Chitwan Medical College, 2021)
Background: Cervical cancer is the fourth most common cancer among women globally. It can be cured if diagnosed at an early stage and treated promptly. This study aimed to find out the awareness on cervical cancer and practice of Pap smear test among the married women of Changunarayan Municipality. Methods: A descriptive cross-sectional study design was carried out in Changunarayan Municipality among 115 purposively selected married women aged between 30 to 60 years. The data was collected from 1stJuly 2021 to 21thJuly 2021. Data was collected by using semi structure interview schedule through face-to-face interview method. Descriptive as well as inferential statistics was used to describe the findings and measure the association between variables. Results: Among the total respondents, 52.2% had inadequate level of awareness and 47.8% had adequate level of awareness in cervical cancer. Regarding the practice, only 20.9% of respondents had done Pap smear test. There is no significant association between level of awareness of cervical cancer with practice of Pap smear test, age, educational status, occupation, age at marriage and age at first child birth of the respondents. Conclusions: It is concluded that women had adequate awareness in cervical cancer however; the practice of performing Pap smear test was low. The level of awareness of cervical cancer did not influence the practice of Pap smear test.